An Econometric Study Of Deforestation In The Brazil's Amazonian Municipalities - Rodolfo Prates; Carlos Bacha (European Regional Science Association (ERSA), 2012)
Brazil has been pointed out as the number one country chop downing tropical native forest. This process takes place especially in the Amazon River Basin Area, which holds the largest tropical forest area in the World and spread over nine different Brazilian states, compounded of 782 cities. However, these cities have different economic structure and different paces of deforestation. Using both analytical and econometric frameworks, this paper evaluates the causes of deforestation in the Brazilian Amazonian municipalities from 2000 to 2004. Starting with an analytical framework, the main causes that led farmers to cut down forests and convert the soil use to other activities are highlighted. Basing on the analytical framework, an equation is developed and estimated using a dynamic panel data model. Agricultural prices, rural credit and government expenditure on transport have played important roles as stimulators for deforestation as well as an inertial process of deforestation has taken place. The article ends by suggesting some policies to restrain deforestation without reducing the income of farmers and the accessibility of the local population.
Keywords: 330